Climatic Impact on Small Grain Production in the Subarctic Region of the United States - Sharratt, B.S.; Knight, C.W.; Wooding, F. (ARCTIC, 2003)
The Subarctic comprises the higher mid-latitudinal regions with short, cool, moist summers and long, cold, dry winters. Indeed, the short, cool growing season is often thought of as a barrier to crop growth and diversity in these regions. Little is known, however, concerning the impact of the Subarctic climate on crop production. This study aimed to identify the climatic factors that are most important to the production of small grains in the Subarctic region of Alaska. The impact of climate on 'Galt' and 'Weal' barley (Hordeum vulgare L.), 'Nip' and 'Toral' oat (Avena sativa L.), and 'Gasser' and 'Park' wheat (Triticum aestivum L.) was assessed using climate and grain yield data collected from 1972 to 1989 at Fairbanks. Multiple regression analysis was used to identify the climatic factors that most influence yield. Different factors accounted for the largest proportion of variability in yield across years for the different grains. 1) For barley, variations in precipitation deficit (pan evaporation minus precipitation) and distribution of precipitation events within a growing season accounted for 41% of the variability across years in yield of Galt and Weal cultivars. 2) For oat, variations in the precipitation deficit ratio (ratio between precipitation deficit and pan evaporation) accounted for 44% of the variability across years in yield of Nip and 58% in yield of Toral oat. 3) For wheat, variations in number of days between precipitation events within a growing season, precipitation deficit, and temperature explained 70% of the variability across years in yield of Gasser and Park wheat. Results from our analysis further indicated that small grain production was bolstered in seasons with greater precipitation, more frequent precipitation, or lower evaporative demand (pan evaporation). Only wheat production appeared to be favored by higher minimum air temperatures. This study suggests that, despite the cool growing season in interior Alaska, the primary climatic limitation to crop production is water stress, ...